2007
DOI: 10.1152/ajprenal.00372.2006
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of epithelial sodium channel in rats with bilateral or unilateral ureteral obstruction

Abstract: .-The roles of epithelial sodium channel (ENaC) subunits (␣, ␤, and ␥) in the impaired renal reabsorption of sodium and water were examined in rat models with bilateral (BUO) or unilateral ureteral obstruction (UUO) for 24 h or with BUO followed by release of obstruction and 3 days of observation (BUO-3dR). In BUO rats, plasma osmolality was increased dramatically, whereas plasma sodium concentration was decreased. Immunoblotting revealed a significantly decreased expression of ␣-ENaC (57 Ϯ 7%), ␤-ENaC (19 Ϯ 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The animal study showed that levels of aldosterone in Munich Wister rats increased after 24 h of UUO compared with the sham rats (404 ± 41 vs. 208 ± 30 pg/mL), and increased significantly in bilateral ureteral obstruction rats (3,610 ± 246 pg/mL). These results suggest that plasma aldosterone concentration is closely related to ureteral ligation [24] . It has been discussed that the intrarenal reninangiotensin system is activated in the obstructed kidney of UUO [25] .…”
Section: Discussionmentioning
confidence: 56%
“…The animal study showed that levels of aldosterone in Munich Wister rats increased after 24 h of UUO compared with the sham rats (404 ± 41 vs. 208 ± 30 pg/mL), and increased significantly in bilateral ureteral obstruction rats (3,610 ± 246 pg/mL). These results suggest that plasma aldosterone concentration is closely related to ureteral ligation [24] . It has been discussed that the intrarenal reninangiotensin system is activated in the obstructed kidney of UUO [25] .…”
Section: Discussionmentioning
confidence: 56%
“…Despite these similarities, it was suggested that the mechanisms underlying the myogenic response in the hydronephrotic kidney model might differ from those of the normal kidney, since it was recently reported by Li et al (22) that ENaC expression in the CCD is rapidly downregulated following ureteral obstruction. This same group (12) had previously surveyed ENaC expression in the rat kidney.…”
Section: Discussionmentioning
confidence: 99%
“…These defects, combined with decreased urinary concentrating capability, increased ANP, and the supernormal volume of fluid and solute, leads to dieresis [95]. In patients with significant obstruction, this impaired concentrating capability may remain long after the obstruction is removed [94][95][96][97]. It is postulated that defects in AQP1 expression are the cause of continued urinary obstruction-associated polyuria [94].…”
Section: Nephrogenic Diabetes Insipidus (Ndi)mentioning
confidence: 99%